Networks in the first global age, 1400-1800 - Rila Mukherjee (ed.) (New Delhi : Indian Council of Historical Research in Association with Primus Books, 2011)
Contributed articles.
Keywords: Navigation; Economic history 19th Century; Economics; Social Sciences